The Application of Comic Strips in Teaching Vocabulary - Lisa Darsalina; Arifin Syamaun; Diana Fauzia Sari (Universitas Syiah Kuala, 2017)
This quantitative study was conducted with the aims to find out students’ vocabulary mastery before and after the application of Comic Strips at reading. The samples were 21 eight-grade students of junior high school. Vocabulary test was given before and after Comic Strips has been applied for four meetings. The findings showed that there was significant improvement of students’ vocabulary mastery in reading. It was found on the students’ pre-test score with level significance degree (a) = 0.05 resulted in tscore = 13.23 ttable t(20,0.05) = 2.086. Since tcount was higher than ttable (tcount ttable), thus Ho was refused or Ha was accepted. It indicates that students’ vocabulary has been increased or improved after the application of teaching reading by using Comic Strips. Based on the findings, the teachers should consider using this technique as an alternative one in reading classroom and activities. The writer also recommends that the other researchers should conduct an analysis study concerning on the students’ point of view regarding to the use of Comic Strips.